Nonlinear Oscillations in Physical Systems - Hayashi, Chūshirō, 1920-2010 (Book collections on Project MUSE., 1985)
Many of today's most exciting questions in the physical and life sciences concern the behavior of nonlinear systems, especially the onset of chaotic behavior under deterministic conditions. Available for the first time in paperback, this book offers a fundamental explanation of nonlinear oscillations in physical systems. Originally intended for electrical engineers, this book remains an important reference for the increasing numbers of researchers studying nonlinear phenomena in physics, chemical engineering, biology, medicine, and other fields. All problems in mechanics are basically nonlinear from the outset, and the linearizations commonly practiced are approximating devices. Focusing attention on those features of problems where nonlinearity results in distinctive new phenomena, the author stresses the relationship between analysis and experiment.